Combined Treatment of Cancer Cells Using Allyl Palladium Complexes Bearing Purine-Based NHC Ligands and Molecules Targeting MicroRNAs miR-221-3p and miR-222-3p: Synergistic Effects on Apoptosis - Chiara Tupini; Matteo Zurlo; Jessica Gasparello; Irene Lodi; Alessia Finotti; Thomas Scattolin; Fabiano Visentin; Roberto Gambari; Ilaria Lampronti (Pharmaceutics, 2023)
Combined treatments employing lower concentrations of different drugs are used and studied to develop new and more effective anticancer therapeutic approaches. The combination therapy could be of great interest in the controlling of cancer. Regarding this, our research group has recently shown that peptide nucleic acids (PNAs) that target miR-221 are very effective and functional in inducing apoptosis of many tumor cells, including glioblastoma and colon cancer cells. Moreover, in a recent paper, we described a series of new palladium allyl complexes showing a strong antiproliferative activity on different tumor cell lines. The present study was aimed to analyze and validate the biological effects of the most active compounds tested, in combination with antagomiRNA molecules targeting two miRNAs, miR-221-3p and miR-222-3p. The obtained results show that a “combination therapy”, produced by combining the antagomiRNAs targeting miR-221-3p, miR-222-3p and the palladium allyl complex 4d, is very effective in inducing apoptosis, supporting the concept that the combination treatment of cancer cells with antagomiRNAs targeting a specific upregulated oncomiRNAs (in this study miR-221-3p and miR-222-3p) and metal-based compounds represents a promising therapeutic strategy to increase the efficacy of the antitumor protocol, reducing side effects at the same time.